Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1073/pnas.89.20.9949
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone modulates a neuronal nicotinic acetylcholine receptor.

Abstract: The major brain nicotinic acetylcholine receptor is assembled from two subunits termed a4 and nal. When expressed in Xenopus oocytes, these subunits reconstitute a functional acetylcholine receptor that is inhibited by progesterone levels similar to those found in serum. In this report, we show that the steroid interacts with a site located on the extracellular part of the protein, thus confirming that inhibition by progesterone is not due to a nonspecific perturbation of the membrane bilayer or to the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(117 citation statements)
references
References 27 publications
5
108
0
2
Order By: Relevance
“…On the other hand, the previous reports have shown that various agents such as serotonin, strychnine, Ca 2+ channel blockers, polyamines, steroids such as progesterone and hydrocortisone, ethanol, and metal ion like Zn 2+ , regulate muscle or neuronal nicotinic acetylcholine receptors expressed in Xenopus oocytes [28][29][30][31][32][33][34][35]. Interestingly, the mechanism (i.e., voltage dependence or competition with acetylcholine for binding site) by which these substances regulate nicotinic acetylcholine receptors depend on the receptor subunit composition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the previous reports have shown that various agents such as serotonin, strychnine, Ca 2+ channel blockers, polyamines, steroids such as progesterone and hydrocortisone, ethanol, and metal ion like Zn 2+ , regulate muscle or neuronal nicotinic acetylcholine receptors expressed in Xenopus oocytes [28][29][30][31][32][33][34][35]. Interestingly, the mechanism (i.e., voltage dependence or competition with acetylcholine for binding site) by which these substances regulate nicotinic acetylcholine receptors depend on the receptor subunit composition.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the involvement of progesterone in multiple receptor systems. Progesterone is known to modulate the release of dopamine (Dluzen and Ramirez, 1990;Ramirez and Zheng, 1996), to act as a functional antagonist at 5-HT3 receptors (Wetzel et al, 1998), as well as to play a role in the control of nicotinic cholinergic receptors (Valera et al, 1992). Given the known sensitivity of PPI to dopaminergic, serotonergic, glutamatergic, and cholinergic systems (Swerdlow and Geyer, 1998;Geyer et al, 2001), the data available so far do not allow us to speculate, which of these systems might be most pertinent to the effects of progesterone in PPI of healthy young women.…”
Section: Ovarian Hormones and Human Sensorimotor Gating V Kumari Et Almentioning
confidence: 99%
“…However, evidence is accumulating that neurosteroids can interact with and regulate the activity of neuronal nAChRs. For instance, progesterone and testosterone inhibit noncompetitively the activity of rat ␣4* receptors ectopically expressed in Xenopus oocytes (Bertrand et al, 1991;Valera et al, 1992;Paradiso et al, 2000). Likewise, progesterone, estradiol, and corticosterone act as noncompetitive antagonists at human ␣3␤4 nAChRs expressed by SH-SY5Y cells (Ke and Lukas, 1996).…”
Section: Steroid Hormones and Neuronal Nachrsmentioning
confidence: 99%
“…Likewise, progesterone, estradiol, and corticosterone act as noncompetitive antagonists at human ␣3␤4 nAChRs expressed by SH-SY5Y cells (Ke and Lukas, 1996). Inhibition of the activation of rat ␣4* nAChRs and human ␣3␤4 nAChRs can be observed within a few seconds of exposure of the receptors to permeant or nonpermeant forms of steroids (Valera et al, 1992;Ke and Lukas, 1996), and is, therefore, the result of the interaction of these compounds with a site(s) located in the extracellular region of the receptors.…”
Section: Steroid Hormones and Neuronal Nachrsmentioning
confidence: 99%